Why we need dedicated insect microphones - A comparison between measurement and MEMS microphone arrays highlights gap in available hardware - Jelto Branding; Dieter von Hörsten; Elias Böckmann; Jens Karl Wegener; Eberhard Hartung (PLoS ONE, 2026)
Acoustic insect recognition could potentially become a key element of insect sensing devices for various applications in pest management and ecological surveying. However, research in this field has yet to bridge the gap between successful laboratory studies and real-world applications. This study reports on extensive experiments and simulations carried out that aim to quantify the influence of different microphone qualities on the prospects of acoustic insect recognition systems that use them. The first microphone used is a four-channel, high-end, low-noise measurement microphone array that represents the cutting edge of acoustic recording capabilities. The second microphone is a low-budget six-channel micro-electro-mechanical system (MEMS) microphone array, initially designed for home voice assistant applications. The study clearly shows that higher-sensitivity microphones will allow for the recording and recognition of much smaller and quieter insects. However, even the simple MEMS microphones can be used to successfully recognise some insects, even in simulated real-world noisy conditions.